Phylogeny, Pathogenicity, and Transmission of H5N1 Avian Influenza Viruses in Chickens - Cui, Jin; Qu, Nannan; Guo, Yang; Cao, Lan; Wu, Siyu; Mei, Kun; Sun, Hailiang; Lu, Yiliang; Qin, Zhifeng; Jiao, Peirong; Liao, Ming (Frontiers in Cellular and Infection Microbiology, 2017)
We analyzed five H5N1 avian influenza viruses (AIVs) isolated from different birds in 2012 in China. Based on whole-genome sequences, we divided the viruses into four genotypes. The DKE26, GSE43 and DKE53 viruses belonged to Genotypes 1–3, respectively. The CKE93 and CKE96 viruses were classified into Genotype 4. Genotypes 1–3 correspond to the viruses containing the HA gene of clade 2.3.2, and Genotype 4 is the virus that bears the HA gene of clade 7.2. To better understand the pathogenicity and transmission of the viruses, we infected chickens with 103 EID50/0.1 ml GSE43 (clade 2.3.2) or CKE93 (clade 7.2) virus. Our results revealed that 6 of 7 specific-pathogen-free (SPF) chickens inoculated with GSE43 virus were dead before 7-day post-infection, but all the SPF chickens inoculated with CKE93 virus survived the infection. Both the GSE43 and CKE93 viruses replicated systemically in chickens. The virus titers of GSE43 virus in tested organs were obviously higher than those of CKE93 virus. Our results revealed that the pathogenicity and replication of GSE43 in chickens was much higher than those of CKE93. The GSE43 virus could transmit between chickens, but the CKE93 could not transmit between chickens by naïve contact. Therefore, different clades of H5N1 AIVs possessed variable pathogenicities and transmission abilities among chickens. Our study contributes to knowledge of pathogenic variations of prevalent H5N1 viruses.